Illuminated pixels the why, what, and how of digital lighting - Wissler, Virginia (Boston, Massachusetts Cengage Learning, 2013)
Teaches digital artists how to apply the foundational principles of lighting to digital lighting and design. This book explores the why, what, and how of lighting, integrating classic concepts with modern techniques, explaining the importance and the application of them.
Keywords: Computer graphics; Lighting -- Computer simulation; Three-dimensional display systems